Simple renal cysts and bovine aortic arch: markers for aortic disease - Adam J Brownstein; Syed Usman Bin Mahmood; Ayman Saeyeldin; Camilo Velasquez Mejia; Mohammad A Zafar; Yupeng Li; John A Rizzo; Neera K Dahl; Young Erben; Bulat A Ziganshin; John A Elefteriades (Open Heart)
Objective This study aimed to assess the prevalence of thoracic aortic disease (TAD) and abdominal aortic aneurysms (AAA) among patients with simple renal cyst (SRC) and bovine aortic arch (BAA).Methods Through a retrospective search for patients who underwent both chest and abdominal CT imaging at our institution from 2012 to 2016, we identified patients with SRC and BAA and propensity score matched them to those without these features by age, gender and presence of hypertension, hyperlipidaemia, diabetes and chronic kidney disease.Results Of a total of 35 498 patients, 6366 were found to have SRC. Compared with the matched population without SRC, individuals with SRC were significantly more likely to have TAD (10.1% vs 3.9%), ascending aortic aneurysm (8.0% vs 3.2%), descending aortic aneurysm (3.3% vs 0.9%), type A aortic dissection (0.6% vs 0.2%), type B aortic dissection (1.1% vs 0.3%) and AAA (7.9% vs 3.3%). The 920 patients identified with BAA were significantly more likely to have TAD (21.8% vs 4.5%), ascending aortic aneurysm (18.4% vs 3.2%), descending aortic aneurysm (6.5% vs 2.0%), type A aortic dissection (1.4% vs 0.4%) and type B aortic dissection (2.4% vs 0.7%) than the matched population without BAA. SRC and BAA were found to be significantly associated with the presence of TAD (OR=2.57 and 7.69, respectively) and AAA (OR=2.81 and 2.56, respectively) on multivariable analysis.Conclusions This study establishes a substantial increased prevalence of aortic disease among patients with SRC and BAA. SRC and BAA should be considered markers for aortic aneurysm development.